2007
DOI: 10.1111/j.1572-0241.2007.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine-Induced Liver Injury in Patients With Inflammatory Bowel Disease: A Systematic Review

Abstract: The mean prevalence of azathioprine (AZA) or 6-mercaptopurine (MP)-induced liver injury in patients with inflammatory bowel disease was approximately 3%, and the mean annual drug-induced liver disorder rate was only 1.4%. However, this low figure calculated from retrospective studies contrasts with a much higher incidence (>10%) reported by a prospective study. Thiopurine-induced hepatotoxicity can be grouped into three syndromes: hypersensitivity, idiosyncratic cholestatic reaction, and endothelial cell injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 78 publications
4
160
1
7
Order By: Relevance
“…The mechanisms of hepatic insult include a drug-induced hepatitis, cholestasis and nodular regenerative hyperplasia of the liver. A recent review found that the mean prevalence of AZA or 6-MP-induced liver injury in patients with IBD was approximately 3%, and mean annual drug-induced liver disorder rate was only 1.4% [Gisbert et al 2007]. In a series of 396 IBD patients taking 6-MP, drug hepatitis was noted in 0.3%.…”
Section: Liver Toxicitymentioning
confidence: 99%
“…The mechanisms of hepatic insult include a drug-induced hepatitis, cholestasis and nodular regenerative hyperplasia of the liver. A recent review found that the mean prevalence of AZA or 6-MP-induced liver injury in patients with IBD was approximately 3%, and mean annual drug-induced liver disorder rate was only 1.4% [Gisbert et al 2007]. In a series of 396 IBD patients taking 6-MP, drug hepatitis was noted in 0.3%.…”
Section: Liver Toxicitymentioning
confidence: 99%
“…Routine liver enzyme monitoring is advised. The medication can be continued with mild abnormalities without clinical symptoms; but should be discontinued when patient develops jaundice or abnormalities persists despite lowering the dose of Azathioprine or 6-MP [118].…”
Section: Thiopurinesmentioning
confidence: 99%
“…Thiopurine-induced liver toxicity is also a relevant issue. It's incidence varies between 3% and 10% of AZA-exposed patients and it can be classified into different entities: hypersensitivity, idiosyncratic cholestatic reaction, and endothelial cell injury (the later resulting in raised portal pressures, venoocclusive disease or peliosis hepatis) [9] . The majority of these syndromes respond to drug withdrawal.…”
Section: Safety Of Azathioprinementioning
confidence: 99%